Secularization in contemporary religious radicalism : an introduction - Simuţ, Corneliu C. (Theological Seminar Series, 2013)
The concept of secularization has grown to become one of the most important features of contemporary religious thought. This book introduces and examines the thinking of sixteen key theologions, philosophers and historians of religion to explain (a) why by the late nineteenth century the traditional concept of God as an ontologically real being came to be considered no longer necessary and (b) how the new perspective on God, which accepts him only as an idea, turned into the preferred approach of today's religion and philosophy, namely "religious radicalism".